2023
DOI: 10.1038/s41467-023-38071-x
|View full text |Cite
|
Sign up to set email alerts
|

IS21 family transposase cleaved donor complex traps two right-handed superhelical crossings

Abstract: Transposases are ubiquitous enzymes that catalyze DNA rearrangement events with broad impacts on gene expression, genome evolution, and the spread of drug-resistance in bacteria. Here, we use biochemical and structural approaches to define the molecular determinants by which IstA, a transposase present in the widespread IS21 family of mobile elements, catalyzes efficient DNA transposition. Solution studies show that IstA engages the transposon terminal sequences to form a high-molecular weight complex and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(21 citation statements)
references
References 85 publications
(114 reference statements)
3
18
0
Order By: Relevance
“…1a ). Note that it has previously been shown that IstA exhibits similar levels of in vitro activity using either the isolated right TIR or an equimolar mixture of left and right TIRs 21 . The donor molecule comprised both a transferred strand, pre-cleaved at a characteristic CA dinucleotide that is typically attacked by transposases and retroviral integrases, and a non-transferred strand bearing a short (5 nucleotide (nt)) 5′ overhang.…”
Section: Istb Aaa+ Promotes Is 21 Transpositionmentioning
confidence: 98%
See 4 more Smart Citations
“…1a ). Note that it has previously been shown that IstA exhibits similar levels of in vitro activity using either the isolated right TIR or an equimolar mixture of left and right TIRs 21 . The donor molecule comprised both a transferred strand, pre-cleaved at a characteristic CA dinucleotide that is typically attacked by transposases and retroviral integrases, and a non-transferred strand bearing a short (5 nucleotide (nt)) 5′ overhang.…”
Section: Istb Aaa+ Promotes Is 21 Transpositionmentioning
confidence: 98%
“…The IS 21 family is particularly widespread, has been found in clinically important multidrug-resistant strains and has shaped the evolution of human pathogens 18 , 19 . Owing to their simplicity and robust activity, IS 21 elements are a particularly appealing model for mechanistic studies 20 , 21 . The archetypal IS 21 sequence contains two terminal inverted repeats (TIRs) that are typically composed of at least two repeated elements (L1 and L2 for the left ends, and R1 and R2 for the right ends) 20 (Fig.…”
Section: Mainmentioning
confidence: 99%
See 3 more Smart Citations